Emission-Tunable and Elastically Bendable Organic Polymorphs for Lasing Media - Tang, Baolei; Tang, Shiyue; Ye, Kaiqi; Zhang, Hongyu (Organic Materials, 2022)
Crystal engineering has served as a powerful strategy to grow organic molecular crystals with different physical behaviors and this strategy has been also attempted for a purpose to grow crystals with desired mechanical properties; however, it is quite challenging to endow all different crystal phases constructed by the same compound with unique reversible deformation, such as elastic bending. We herein report a rare example of all-polymorph elastic crystals accompanied by precisely tunable emission colors. Single-crystal structure analyses and their optical and mechanical properties have been fully investigated on all polymorphs. The color-tunable amplified spontaneous emissions of both the straight and elastically bent polymorphs demonstrate the applicability of these elastic polymorphs in future wearable optoelectronic devices.
Keywords: organic polymorphs; crystal structures; elastic deformation; mechanical properties; amplified spontaneous emission